Medical problems of adults who were sexually abused in childhood. Issue 6726 (17th March 1990) - Arnold, R P; Rogers, D; Cook, D A
Abstract : The aim of the study was to see whether adults who had been sexually abused in childhood were vulnerable to physical symptoms and therefore investigation and intervention. The case histories of seven patients who were aged 22-39, were under the care of three consultant psychiatrists, had experienced childhood sexual abuse, and had a history of medical or surgical intervention were surveyed. The patients had had a mean of 18 contacts with non-psychiatric consultant teams and a mean of eight operations, with a high rate (66-70%) of normal findings. They had experienced many somatic symptoms, which led to investigations and interventions in the specialties of gynaecology, obstetrics, gastroenterology, urology, rheumatology, haematology, orthopaedics, neurology, and neuropsychiatry. The history of childhood sexual abuse was recognised only in the later stages of this medical and surgical intervention. The possibility of childhood sexual abuse should be considered earlier in such cases to prevent further unnecessary intervention.